Association between gender and short-term outcome in patients with ST elevation myocardial infraction participating in the international, prospective, randomised Administration of Ticagrelor in the catheterisation Laboratory or in the Ambulance for New ST elevation myocardial Infarction to open the Coronary artery (ATLANTIC) trial: a prespecified analysis. Issue 9 (21st September 2017) - Venetsanos, Dimitrios; Sederholm Lawesson, Sofia; Alfredsson, Joakim; Janzon, Magnus; Cequier, Angel; Chettibi, Mohamed; Goodman, Shaun G; van't Hof, Arnoud W; Montalescot, Gilles; Swahn, Eva
Abstract : Objectives: To evaluate gender differences in outcomes in patents with ST-segment elevation myocardial infarction (STEMI) planned for primary percutaneous coronary intervention (PPCI). Settings: A prespecified gender analysis of the multicentre, randomised, double-blind Administration of Ticagrelor in the catheterisation Laboratory or in the Ambulance for New ST elevation myocardial Infarction to open the Coronary artery. Participants: Between September 2011 and October 2013, 1862 patients with STEMI and symptom duration <6 hours were included. Interventions: Patients were assigned to prehospital versus in-hospital administration of 180 mg ticagrelor. Outcomes: The main objective was to study the association between gender and primary and secondary outcomes of the main study with a focus on the clinical efficacy and safety outcomes. Primary outcome: the proportion of patients who did not have 70% resolution of ST-segment elevation and did not meet the criteria for Thrombolysis In Myocardial Infarction (TIMI) flow 3 at initial angiography. Secondary outcome: the composite of death, MI, stent thrombosis, stroke or urgent revascularisation and major or minor bleeding at 30 days. Results: Women were older, had higher TIMI risk score, longer prehospital delays and better TIMI flow in the infarct-related artery. Women had a threefold higher risk for all-cause mortality compared with men (5.7% vs 1.9%, HR 3.13, 95% CI 1.78 to 5.51). After adjustment, the difference was attenuated but remained statistically significant (HR 2.08, 95% CI 1.03 to 4.20). The incidence of major bleeding events was twofold to threefold higher in women compared with men. In the multivariable model, female gender was not an independent predictor of bleeding (Platelet Inhibition and Patient Outcomes major HR 1.45, 95% CI 0.73 to 2.86, TIMI major HR 1.28, 95% CI 0.47 to 3.48, Bleeding Academic Research Consortium type 3–5 HR 1.45, 95% CI 0.72 to 2.91). There was no interaction between gender and efficacy or safety of randomised treatment. Conclusion: In patients with STEMI planned for PPCI and treated with modern antiplatelet therapy, female gender was an independent predictor of short-term mortality. In contrast, the higher incidence of bleeding complications in women could mainly be explained by older age and clustering of comorbidities. Clinical trial registration: NCT01347580;Post-results.